Fasting Blood Glucose Levels in Adult Women with Type 2 Diabetes Mellitus and Its Associated Factors - Dewi, Dwi Hananta; Probandari, Ari Natalia; Indarto, Dono (Jurusan Keperawatan FIKES UNSOED, 2018)
AbstractIndonesia has the sixth largest number of people with diabetes in the world. This study aimed to investigate association of age of menarche, duration of diabetes, vitamin c (VC) intake and psychological stress with fasting blood glucose (FBG) levels in adult women with type 2 diabetes mellitus (T2DM). Psychological stress was measured using a STAI questionnaire, while anthropometry, duration of diabetes and age of first menarche were assessed using open questionnaires. Vitamin C intake and FBG level were measured using SQ-FFQ and the hexokinase method respectively. Data were analyzed using Spearman Rank correlation and multiple linear regression tests. A total of 188 adult women with T2DM had mean age 53±5.31 years old, Body Mass Index (BMI) 25±3.76 kg/m2, age at menarche 13.8±1.71 years old, duration of diabetes 4.4±3.38 years and VC 56.9±46.79 mg/day. Body Mass Index (r=-0.190 p=0.011) and VC intake (r=-0.153 p=0.049) were associated with FBG levels. While, age of menarche, duration of diabetes and psychological stress were not associated with FBG levels.AbstrakIndonesia menempati peringkat keenam terbesar jumlah penderita diabetes melitus (DM) di dunia. Tujuan penelitian ini adalah menganalisis hubungan usia menarche, lama menderita DM tipe 2 (DMT2), asupan vitamin c (VC) dan stres psikologis dengan kadar glukosa darah puasa (GDP) pada perempuan dengan DMT2 Stres psikologis diukur menggunakan kuesioner STAI sedangkan data antropometri, lama menderita T2DM dan usia menstruasi dikaji dengan kuisioner terbuka. Asupan vitamin C ditentukan dengan Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) dan kadar GDP serum diukur dengan metode hexokinase. Data kemudian dianalisis dengan menggunakan Korelasi Spearman dan regresi linier ganda. Sebanyak 188 subjek memiliki rata-rata usia 53+5,31 tahun, IMT 25+3,76 kg/m2, lama menderita DMT2 4,4+3,38 tahun, usia mesntruasi 13,8+1,71 tahun dan asupan VC 56,9±46,79 mg/day. Indeks Massa Tubuh (r=-0.190; p=0,011) dan asupan VC (r=-0,153; p=0,049) berhubungan dengan kadar GDP. Sementara itu usia menstruasi, lama menderita DM dan stress psikologi tidak berhubungan dengan kadar GDP.